PLGA-Based Nanomedicine: History of Advancement and Development in Clinical Applications of Multiple Diseases - Hashem O. Alsaab; Fatima D. Alharbi; Alanoud S. Alhibs; Nouf B. Alanazi; Bayan Y. Alshehri; Marwa A. Saleh; Fahad S. Alshehri; Majed A. Algarni; Turki Almugaiteeb; Mohammad N. Uddin; Rami M. Alzhrani (MDPI AG, 2022)
Research on the use of biodegradable polymers for drug delivery has been ongoing since they were first used as bioresorbable surgical devices in the 1980s. For tissue engineering and drug delivery, biodegradable polymer poly-lactic-co-glycolic acid (PLGA) has shown enormous promise among all biomaterials. PLGA are a family of FDA-approved biodegradable polymers that are physically strong and highly biocompatible and have been extensively studied as delivery vehicles of drugs, proteins, and macromolecules such as DNA and RNA. PLGA has a wide range of erosion times and mechanical properties that can be modified. Many innovative platforms have been widely studied and created for the development of methods for the controlled delivery of PLGA. In this paper, the various manufacturing processes and characteristics that impact their breakdown and drug release are explored in depth. Besides different PLGA-based nanoparticles, preclinical and clinical applications for different diseases and the PLGA platform types and their scale-up issues will be discussed.